The role of ovarian reserve markers in prediction of clinical pregnancy. (19th May 2017) - Zebitay, Ali G.; Cetin, Orkun; Verit, Fatma F.; Keskin, Seda; Sakar, M. Nafi; Karahuseyinoglu, Sercin; Ilhan, Gulsah; Sahmay, Sezai
Abstract: To evaluate the role of ovarian reserve markers in the prediction of clinical pregnancy and embryo transfer accomplishment among poor responder IVF applicants. 304 female poor responder IVF applicants were included in this prospective cohort study conducted at the IVF-unit. Antral follicle count, FSH, LH, E2, AMH and IVF outcomes were compared in pregnant and non-pregnant groups as well as in ET vs. non-ET groups. The number of retrieved oocytes was significantly correlated positively with AMH and AFC, and negatively with FSH and age. Quartiles of FSH and AFC were similar to the rate of pregnancy. Quartiles of AMH (<25%/25–75% and <25%/>75%) were statistically significant. Mean serum levels for AMH were significantly lower in the non-ET group. Our findings seem to indicate that day 3 AMH values can predict ET accomplishment with a sensitivity of 96% and a specificity of 35%. Quartiles of AMH <25% (< 0.21 ng/mL) can predict the IVF results among poor responder IVF applicants. Impact statement: Various cut-off values have been determined for day 3 serum AMH values. These values help to determine the groups that are expected to give normal, high or low response to stimulation and decide the treatment options. In contrast to other groups of patients, poor responders cannot reach the embryo transfer stage for several reasons. These are; absence of a mature oocyte after oocyte pick-up, fertilisation failure without male factor or poor embryo quality. In the present study; a cut-off value of 0.33 ng/mL for the prediction of ET accomplishment in poor responder patients was determined with a sensitivity of 96%. Additionally, clinical pregnancy could not be achieved under the value of 0.21 ng/mL day 3 AMH values. It is important to clarify the embryo transfer success of poor responder patients prior to expected treatment success. Pre-treatment counselling for these patients would lessen the disappointment that may develop after treatment. The cost-effectiveness of treatments below these AMH values can be determined by further studies.